2014
DOI: 10.1002/jmv.23972
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus: Prevalence and factors associated in women prisoners population from the Eastern Brazilian Amazon

Abstract: This study aimed to examine the prevalence of human papillomavirus (HPV) and the associated factors among female prisoners in Ananindeua City, State of Pará, Brazil. In 2010, 190 cervical samples were obtained, and Pap smear and polymerase chain reaction (GE Health Care™, Uppsala, Sweden) were performed. Additionally, a questionnaire was used. The prevalence of HPV was 10.5%, and the presence of cervical intraepithelial neoplasia grade I (n = 33, 17.5%; P < 0.1) was associated with HPV infection. The presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
1
9
0
1
Order By: Relevance
“…Several studies have been conducted around Brazil. The prevalence rates range from 10·5% to 48·6% [19][20][21][22][23][24][25][26][27]. In this study, we detected a high prevalence of HPV infection in Southern Bahia (47·7%, 95% CI 40·8-54·7), which is similar to the prevalence reported in Rio de Janeiro [27], and higher when compared with other regions including Salvador, the Capital of Bahia State [23,28].…”
Section: Discussionsupporting
confidence: 78%
“…Several studies have been conducted around Brazil. The prevalence rates range from 10·5% to 48·6% [19][20][21][22][23][24][25][26][27]. In this study, we detected a high prevalence of HPV infection in Southern Bahia (47·7%, 95% CI 40·8-54·7), which is similar to the prevalence reported in Rio de Janeiro [27], and higher when compared with other regions including Salvador, the Capital of Bahia State [23,28].…”
Section: Discussionsupporting
confidence: 78%
“…The results of the current study are consistent with those of other studies regarding HPV detection in Brazilian women. de Aguiar Original Article et al, 25 Lorenzi et al, 19 Rosa et al, 26 and Nonnenmacher et al 27 reported HPV prevalence rates of 10.5%, 12.3%, 12.3%, and 15%, respectively. The majority of these women lived in rural or remote areas of Brazil and experienced difficulties in accessing medical care or the heath assistance infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Among the women who underwent colposcopies, 92.8% (103 of 111 women) were infected with hr-HPV, 43.2% (48 of 111 women) were diagnosed with CIN21, and 32.4% (36 of 111 women) were classified as having unsatisfactory findings because the transformation zone or the endocervical borders of the lesion were not identified during the examination. 25 Based on these results, the HPV DNA test demonstrated accuracy, with a sensitivity of 100% (95% confidence interval, 75.3%-100%) and a specificity of 10.8% (95% confidence interval, 5.1%-19.6%), considering the cervical biopsy as the gold standard. However, if biopsy was not performed, colposcopy was considered the gold standard (59.4% of the women referred for follow-up [66 of 111 women] did not undergo the procedure).…”
Section: Molecular Test Performancementioning
confidence: 91%
“…Essa infecção ocor-DOI: http://dx.doi.org /10.12957/reuerj.2017.25823 re preferencialmente nos órgãos genitais como a vulva, vagina, colo do útero, pênis, áreas perianais e ainda na orofaringe. Caso não sejam tratadas, podem evoluir para o câncer 1 . O HPV é agrupado em genótipos considerados de baixo e alto risco oncogênico, buscando estabelecer uma relação entre a infecção persistente, seus tipos virais e o câncer cervical 2 .…”
Section: Introductionunclassified